The effect of flashcard-based vocabulary games on fourth-grade students’ vocabulary understanding - Fakhri Khusaini; Leni Lutfiani; Ika Irawati (Universitas Merdeka Malang, 2025)
One of the main challenges students face in learning English is limited vocabulary understanding, often due to insufficient learning materials and outdated instructional approaches. Flashcards are a visual tool that can support vocabulary learning through image–word associations. This study aimed to investigate the effect of flashcard-based vocabulary games on fourth-grade students’ vocabulary understanding at a public elementary school in West Nusa Tenggara. Using a pre-experimental one-group pretest–posttest design, the study involved 20 students selected through purposive sampling. Data were collected through vocabulary tests, observation sheets, and student questionnaires. The vocabulary test assessed two components: spelling and meaning comprehension. Data analysis included normality and homogeneity tests, and a paired-samples t-test, using IBM SPSS Statistics 24. The results showed a significant improvement in students’ vocabulary understanding after the implementation of flashcards. The mean pretest score increased from 59.25 to 82.00 in the posttest, and the number of students achieving mastery rose from 5 to 19. The paired-samples t-test yielded a p-value of 0.000 (< 0.05), indicating a statistically significant difference between pretest and posttest scores. These findings demonstrate that flashcard-based vocabulary games effectively enhance students’ vocabulary understanding and can be used to support English learning in elementary school settings.